Surface rainfall erosion resistance and freeze-thaw durability of bio-cemented and polymer-modified loess slopes. (1st January 2022) - Sun, Xiaohao; Miao, Linchang; Chen, Runfa; Wang, Hengxing; Xia, Jingxin
Abstract: Microbially induced calcite precipitation (MICP) has been shown to mitigate sand erosion; however, few studies have applied MICP on loess soils. In this study, polyacrylamide (PAM) was added to the cementation solution, and combined MICP-PAM treatment was applied to improve the surface erosion resistance of loess-slopes. The freeze-thaw (FT) durability of MICP-PAM treated loess slopes was also studied. The obtained results showed that MICP-PAM treatment improved erosion resistance and addition of 1.5 g/L PAM achieved the best erosion control and highest surface strength. The high erosion resistance of MICP-PAM treated slopes could be attributed to the stable spatial structure of precipitation, and PAM addition conveyed stronger resistance to tension or shear force. With increasing number of FT cycles, the surface strength of MICP-PAM treated loess slopes decreased; however, slopes subjected to 12 FT cycles still only lost little soil. In MICP-PAM treated loess slopes, cracks and pores evolved with increasing number of FT cycles. With increasing number of FT cycles, porosity and fractal dimension increased, pore ellipticity decreased slightly, and the percentage of various pores changed slightly. The number of FT cycles had less effect on MICP-PAM treated loess slopes than on untreated slopes. MICP-PAM treatment significantly mitigated surface erosion of loess-slopes and improved FT weathering resistance, thus presenting promising potential for application in the field. In addition, based on the linear correlations between surface strength and rainfall-erosion resistance, surface strength could be measured to evaluate the rainfall-erosion resistance for MICP-PAM treated slopes in practical engineering applications. Highlights: Microbially-induced calcite precipitation (MICP) application was studied. The MICP application improves erosion resistance of loess-slopes. Further, polyacrylamide (PAM) was added to provide additional erosion resistance. MICP-PAM treatment ensured a stronger freeze-thaw weathering resistance.